2018
DOI: 10.11114/aef.v5i2.2944
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Transmission between Oil and LME Futures

Abstract: This paper investigates the volatility transmission between oil and base metals to assess the possibility of hedge strategy across commodity markets. In order to identify the volatility linkage of oil to the base metals, the bivariate GARCH model is applied using daily returns data period over 2000-2016. It is found that evidence of volatility transmission between oil and base metals is somewhat strong with a 1% significant level. This result suggests the investment idea of commodity hedging strategy of cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The results showed that LME's volatility was larger post-crisis when compared to pre-crisis. 4 Ewing and Malik (2013) found the linkage that existed between the volatilities in oil and gold, while Park (2018) found evidence of volatility transmission between oil and base metals thanks to the financialization of the commodity markets. This evidence suggests that there was a somewhat synchronized boom and bust cycle within the commodities.…”
Section: The Joint Hypothesis Testmentioning
confidence: 99%
“…The results showed that LME's volatility was larger post-crisis when compared to pre-crisis. 4 Ewing and Malik (2013) found the linkage that existed between the volatilities in oil and gold, while Park (2018) found evidence of volatility transmission between oil and base metals thanks to the financialization of the commodity markets. This evidence suggests that there was a somewhat synchronized boom and bust cycle within the commodities.…”
Section: The Joint Hypothesis Testmentioning
confidence: 99%
“…However, the long-only index funds might be beneficial, thanks to investments by speculators. Park (2018) found that the evidence of volatility transmission between oil and base metals was somewhat strong, with a 1% significant level. He argued that considering this result, the behavior of volatility in oil and LME futures prices applied to hedge decisions across the commodity market was useful.…”
Section: Literature Reviewmentioning
confidence: 98%
“…5 They found no evidence that the volatilities processes were fractionally cointegrated. Park (2018) provided evidence of volatility transmission between oil and the base metals through the bivariate GARCH model. Within the results, he argued that hedging decisions across the oil and LME futures were feasible to deal with market risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The LME (London Metal Exchange) 1 is the world's largest futures exchange in the metal industry, including for six base metals-copper, aluminum, lead, zinc, tin, and nickel-and is known for being quite correlated with the business cycle (Park 2018). Based on Bloomberg data, the LME is truly a global commodity exchange, as 95% of trades originate from overseas.…”
Section: Introductionmentioning
confidence: 99%